2014
DOI: 10.3892/br.2014.267
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effects of naringenin in rats with spinal nerve ligation-induced neuropathic pain

Abstract: Abstract. Naringenin, a flavonoid abundant in citrus fruits, such as grapefruits, has been reported to possess anti-inflammatory properties. The present study aimed to investigate the analgesic potential of naringenin in L5 spinal nerve ligation (SNL)-induced peripheral neuropathic pain and the underlying mechanisms associated with neuroinflammation. Different doses of naringenin or saline were administered intrathecally once daily for 11 consecutive days, from 3 days prior to surgery to 7 days after surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…The present study indicated that NAR inhibited microglia activation-mediated neuroinflammation. These results were consistent with the previous studies that NAR alleviated neuropathic pain through inhibiting microglia-induced neuroinflammation (Hu and Zhao, 2014).…”
Section: Discussionsupporting
confidence: 94%
“…The present study indicated that NAR inhibited microglia activation-mediated neuroinflammation. These results were consistent with the previous studies that NAR alleviated neuropathic pain through inhibiting microglia-induced neuroinflammation (Hu and Zhao, 2014).…”
Section: Discussionsupporting
confidence: 94%
“…Other than in citrus fruits, naringenin also contain in honey. Study reports naringenin to have analgesic effect in inhibiting neuropathic pain on rats (Kaulaskar et al, 2012;Hu and Zhao, 2014). The result also demonstrates that narigenin reduced lipid peroxidation and nitric oxide.…”
Section: Analgesic Effects Of Honey and Potentials In Morphine Tolerance Studymentioning
confidence: 79%
“…Glial activation leads to a pro-inflammatory response with pathological effects, such as neuronal hyperexcitability, chronic neurotoxicity, and inflammation, which improves neuropathic healing. 24 Abnormal activation of microglia produces a primary cellular response that plays an essential role in the pathogenesis of the inflammatory response. 15,18 Specific cytokines released during the inflammatory process play an important role in the development of two modalities of hyperalgesia (thermal and mechanical), so that maintenance of inflammation plays an important role in chronic healing.…”
Section: Pathogenesis Of Inflammatory Pain In Hnpmentioning
confidence: 99%